The complex study of folklore: the multidisciplinary and interdisciplinary approaches - Ibrayeva*, E.E.; Abilkassym, M.A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The 21st century has seen a significant increase in complex processes in the sciences and humanities. The importance and necessity of integrative research are clearly evidenced by the humanities, including folklore and folk studies. In this regard, folklore faced the objective need to re-evaluate its developmental tendency and clarify the object of its study in the context of a radical change in the place and role of folklore in modern science. The scientific approaches that developed earlier in folklore, including multidisciplinary ones, do not always allow characterizing with sufficient completeness the completely modern folklore process. Moreover, this circumstance poses new tasks for modern folklore, for the complex study of folklore. In order to contribute to the realization of this task, a scientific article on «The complex study of folklore: the multidisciplinary and interdisciplinary approaches» is proposed. Starting from the theoretical and methodological basis, the article analyzes the problems and possibilities of comprehensive study of folklore tradition and its prospects in terms of synergetic theory. In the course of the work comparative-contrastive, inductive and narrative analyzes were applied. The obtained results show that the term «complex study» includes multidisciplinary and interdisciplinary approaches in folklore study. Each of them has its own capabilities that create a unified scientific basis of folklore studies. An integrated model for the study of folklore implies a single scientific methodology, a single subject, and a single set of scientific tools.